The effect of trade openness on nationalism - Azisman, Aidzat Famirul (2019)
There is a re-emergence of nationalism among countries in recent years, contradicting the globalization process that is perceived to have grown rapidly in the last decade. Initially, the entire focus of this paper was on the global scale, aim on finding the relationship between foreign trade and domestic trade, foreign trade and nationalism, and ideologies of region and the region’s economy. The intent of this paper is to examine the effect of economic openness on nationalism, with details of trade also be discussed which may relate to the aim of this paper as well. A paper by Lan and Li (2014) has developed an economic framework in examining the effect of economic openness of a country or region on nationalism. This study uses the European Value Survey, ranging from 1981 to 2009. The highest number of respondents (or observation) accounts to 164,997 respondents. Overall, the obstacles faced during this study make it difficult to come into a definite result. However, even though it is not strong enough, this paper’s findings have also found some evidence that there is an effect of trade openness on nationalism.